Factors Associated with Noncompletion of Latent Tuberculosis Infection Treatment in an Inner-City Population in Edmonton, Alberta - Kathy Malejczyk; Jennifer Gratrix; Avril Beckon; Danusia Moreau; Gwenna Williams; Dennis Kunimoto; Rabia Ahmed (Canadian Journal of Infectious Diseases and Medical Microbiology)
A limited number of studies have been published that examine treatment completion rates and interventions used to increase treatment completion within an inner-city population. The purpose of the present study was to determine the rate of latent tuberculosis infection (LTBI) treatment completion in an inner-city population in Edmonton, Alberta, and to identify factors that correlated with treatment completion. A retrospective chart review was conducted involving patients who started LTBI treatment between January 1, 2005 and December 31, 2010 in Edmonton’s inner city. A total of 77 patients started treatment and 57 (74%) patients completed LTBI treatment. Homelessness was the only variable that was significantly associated with incomplete treatment (OR 8.0 [95% CI 1.4 to 45.6]) and it remained significant when controlling for drug use (adjusted OR 6.5 [95% CI 1.1 to 38.8]). While the present study demonstrated treatment completion rates comparable with or better than those described in the general population, it highlighted the need for continued emphasis on interventions aimed at improving outcomes within homeless populations.